1998
DOI: 10.1038/1099
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic regulation of cerebral cortical microcirculation

Abstract: Functional variations in cerebral cortical activity are accompanied by local changes in blood flow, but the mechanisms underlying this physiological coupling are not well understood. Here we report that dopamine, a neurotransmitter normally associated with neuromodulatory actions, may directly affect local cortical blood flow. Using light and electron-microscopic immunocytochemistry, we show that dopaminergic axons innervate the intraparenchymal microvessels. We also provide evidence in an in vitro slice prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
177
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(184 citation statements)
references
References 27 publications
5
177
0
1
Order By: Relevance
“…27 Injection of D 2 -like receptor antagonist also reduced the striatal negative fMRI responses evoked by noxious forepaw stimuli. 5,6,10 These results, in line with an earlier report, 28 implied that dopamine and its receptors can regulate regional microcirculation. We recently showed that the striatal CBV decreases in this stimulation model is associated with the integrity of the dopaminergic innervation.…”
Section: Neurovascular Responses In the Striatumsupporting
confidence: 90%
“…27 Injection of D 2 -like receptor antagonist also reduced the striatal negative fMRI responses evoked by noxious forepaw stimuli. 5,6,10 These results, in line with an earlier report, 28 implied that dopamine and its receptors can regulate regional microcirculation. We recently showed that the striatal CBV decreases in this stimulation model is associated with the integrity of the dopaminergic innervation.…”
Section: Neurovascular Responses In the Striatumsupporting
confidence: 90%
“…Several studies investigated dopaminergic regulation of cerebral microcirculation (47,48). The study by Choi et al (48) is particularly relevant.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation presumes that dopamine is released in increased amounts to unexpected rewards (Montague et al, 1996;Schultz et al, 1997;Schultz, 1998). Dopamine can decrease neuronal excitability (Cooper et al, 1996) and may also directly constrict the microvasculature (Krimer et al, 1998), but increased accumbens activity has also been associated with the subjective pleasure of cocaine (Breiter et al, 1997). These findings suggest that our observed increase in activation with unpredictability could be related to increased dopamine release, either because the accumbens projects to the VTA or because it receives a projection from the VTA, either of which would be consistent with the model results.…”
Section: Discussionmentioning
confidence: 99%